Determination of the spent fuel decay heat with the VERA core simulator - Kromar, Marjan; Godfrey, Andrew T. (Frontiers in Energy Research, 2022)
VERA core simulator capabilities to predict spent fuel decay heat have been explored. The comparison with the Serpent2 and NEWT/TRITON sequence from the SCALE package, performed on the NPP Krško fuel test cases, has enabled the validation of the VERA calculation sequence. Since the VERA is a 3-D core simulator, the focus in the rest of the paper was on the investigation of the 3-D effects and nonlinearity of the soluble boron concentration averaging process, which are difficult to assess with most of available computational tools. A difference in the decay heat prediction between the 3-D and 2-D model approaches was analyzed. In addition, the impact of the Inconel grids on the decay heat was determined. Averaging the concentration of soluble boron over the fuel irradiation period has been found to be a viable approach, since it results in slight decay heat overprediction, which is considered conservative for most applications. Finally, demonstration on the Watts Bar Unit 1 cycle 1 depletion has shown formidable VERA capabilities to accurately predict spent fuel decay heat.